YouTube in higher education: comparing student and instructor perceptions and practices - Greeves, Scott; Oz, Mustafa (Frontiers in Education, 2024)
YouTube is widely adopted in educational settings because it can support a variety of learning practices. However, unlike traditional learning resources, YouTube videos lack a standardized quality assurance process, posing a significant concern for educational users. The responsibility of identifying suitable educational content falls on the individual user as they navigate the site and select videos. Despite its importance, the multi-step process of video selection remains poorly understood among educational users. While it is established that most users begin with a keyword search for their topic of interest, there is limited empirical evidence on how users deliberate between returned video options, considering features such as view count and comment section sentiment, to make an informed video selection. To address this knowledge gap, this study surveyed college (1) instructors (N = 61) and ( 2) students (N = 300) to compare their prioritization of ten YouTube video features in relation to video selection. The results revealed fundamental similarities in their prioritization of key aspects such as accuracy, content creators' expertise, video duration, and style. However, the analyses also suggest that instructors and students may value differing platform affordances across YouTube's features.